Martin Davis: An Overview of his Work in Logic, Computer Science, and Philosophy - De Mol, Liesbeth; Matiyasevich, Yuri V; Omodeo, Eugenio G; Policriti, Alberto; Sieg, Wilfried; Weyuker, Elaine J (Philosophia mathematica)
Abstract In his autobiographical essay written in 1999, ‘From logic to computer science and back’, Martin David Davis (1928 3 8–2023 1 1) indicated that he viewed himself as a logician and a computer scientist. He expanded the essay in 2016 and expressed a new perspective through a changed title, ‘My life as a logician’. He points out that logic was the unifying theme underlying his scientific career. Our paper attempts to provide a consistent vision that illuminates Davis’s successive contributions leading to his landmark writings on computability, unsolvable problems, automated reasoning, as well as the history and philosophy of computing.